2021
DOI: 10.1109/access.2021.3082424
|View full text |Cite
|
Sign up to set email alerts
|

Know You Neighbor: Fast Static Prediction of Test Flakiness

Abstract: Context: Flaky tests plague regression testing in Continuous Integration environments by slowing down change releases and wasting testing time and effort. Despite the growing interest in mitigating the burden of test flakiness, how to efficiently and effectively detect flaky tests is still an open problem.Objective: In this study, we present and evaluate FLAST, an approach designed to statically predict test flakiness. FLAST leverages vector-space modeling, similarity search, dimensionality reduction, and k-Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[26]. This shows that the availability of language-specific artifacts is a concern not only to dynamic, but also to static and hybrid approaches, that use them to extract code smells [25], data dependencies [26], or the vocabulary of tests [27], [28], or to measure complexity metrics [24].…”
Section: A Using Instrumentation or Language-specific Artifacts To De...mentioning
confidence: 98%
See 1 more Smart Citation
“…[26]. This shows that the availability of language-specific artifacts is a concern not only to dynamic, but also to static and hybrid approaches, that use them to extract code smells [25], data dependencies [26], or the vocabulary of tests [27], [28], or to measure complexity metrics [24].…”
Section: A Using Instrumentation or Language-specific Artifacts To De...mentioning
confidence: 98%
“…To address this demand, researchers have proposed many flakiness detection approaches [15]- [28]. We found most of these difficult to implement in an industrial setting, since they rely on code instrumentation [15]- [20], which is not always implementable, demand multiple test reruns [19]- [23], which is computationally demanding, or require language-specific artifacts [24]- [28]. Our observation is underlined by a recent study that found the adoption rates of automated flakiness detection techniques among practitioners to be poor [29].…”
Section: Introductionmentioning
confidence: 99%
“…The flaky tests have gained wide attention in the CI field [37,38]. Many researchers have focused on the research about flaky tests, for example, flakiness predicting [39][40][41], the lifecycle of flaky tests [42] and the impact of flaky tests on TCP [1,10]. In our work, we compare the effectiveness of SatTCP and baseline approaches on both flaky tests and nonflaky tests, respectively, to investigate the impact of flaky tests on the performance of TCP methods.…”
Section: Tcp In CImentioning
confidence: 99%
“…Silva et al[51] focus on detecting asynchronous wait and concurrency flakiness by introducing environment noise. Many works[1,9,21,39,55] apply machine learning for flakiness detection. Mitigation and Repair.…”
mentioning
confidence: 99%